Microwave-assisted chemistry: synthetic applications for rapid assembly of nanomaterials and organics - Gawande, Manoj B; Shelke, Sharad N; Zboril, Radek; Varma, Rajender S (Accounts of chemical research, 2014)
The magic of microwave (MW) heating technique, termed the Bunsen burner of the 21st century, has emerged as a valuable alternative in the synthesis of organic compounds, polymers, inorganic materials, and nanomaterials. Important innovations in MW-assisted chemistry now enable chemists to prepare catalytic materials or nanomaterials and desired organic molecules, selectively, in almost quantitative yields and with greater precision than using conventional heating. By controlling the specific MW parameters (temperature, pressure, and ramping of temperature) and choice of solvents, researchers can now move into the next generation of advanced nanomaterial design and development. Microwave-assisted chemical reactions are now well-established practices in the laboratory setting although some controversy lingers as to how MW irradiation is able to enhance or influence the outcome of chemical reactions. Much of the discussion has focused on whether the observed effects can, in all instances, be rationalized by purely thermal Arrhenius-based phenomena (thermal microwave effects), that is, the importance of the rapid heating and high bulk reaction temperatures that are achievable using MW dielectric heating in sealed reaction vessels, or whether these observations can be explained by so-called "nonthermal" or "specific microwave" effects. In recent years, innovative and significant advances have occurred in MW hardware development to help delineate MW effects, especially the use of silicon carbide (SiC) reaction vessels and the accurate measurement of temperature using fiber optic (FO) temperature probes. SiC reactors appear to be good alternatives to MW transparent borosilicate glass, because of their high microwave absorptivity, and as such they serve as valuable tools to demystify the claimed magical MW effects. This enables one to evaluate the influence of the electromagnetic field on the specific chemical reactions, under truly identical conventional heating conditions, wherein temperature is measured accurately by fiber optic (FO) probe. This Account describes the current status of MW-assisted synthesis highlighting the introduction of various prototypes of equipment, classes of organic reactions pursued using nanomaterials, and the synthesis of unique and multifunctional nanomaterials; the ensuing nanomaterials possess zero-dimensional to three-dimensional shapes, such as spherical, hexagonal, nanoprisms, star shapes, and nanorods. The synthesis of well-defined nanomaterials and nanocatalysts is an integral part of nanotechnology and catalysis science, because it is imperative to control their size, shape, and compositional engineering for unique deployment in the field of nanocatalysis and organic synthesis. MW-assisted methods have been employed for the convenient and reproducible synthesis of well-defined noble and transition core-shell metallic nanoparticles with tunable shell thicknesses. Some of the distinctive attributes of MW-selective heating in the synthesis and applications of magnetic nanocatalysts in organic synthesis under benign reaction conditions are highlighted. Sustainable nanomaterials and their applications in benign media are an ideal blend for the development of greener methodologies in organic synthesis; MW heating provides superb value to the overall sustainable process development via process intensification including the flow systems.